Applying the Shrinkage Technique for Estimating the Scale Parameter of Weighted Rayleigh Distribution - Hassoun, Intesar Obeid; Hussein, Adel Abdulkadhim (Iraqi Journal of Science, 2020)
This paper includes the estimation of the scale parameter of weighted Rayleigh distribution using well-known methods of estimation (classical and Bayesian). The proposed estimators were compared using Monte Carlo simulation based on mean squared error (MSE) criteria. Then, all the results of simulation and comparisons were demonstrated in tables.